Influence of powdered bamboo filler content on the tensile strength and fatigue life of epoxy composites - Chaiki Malakar; Hrishikesh Dutta; Sumit Bhowmik; Ravivarman R; Mridusmita Roy Choudhury (Materials Research Express)
The aim of this study is to evaluate the influence of reinforcing powdered bamboo filler (PBF) on the mechanical and fatigue properties of epoxy-based polymer composites, with a focus on balancing void content and tensile strength. Epoxy composites were fabricated by incorporating varying content of PBF (2.5%, 5%, 7.5%, 10%, and 12.5% by weight) using casting process, at room temperature (32 °C–34 °C) for 24–48 h. The prepared samples were subjected to mechanical testing (tensile strength), fatigue analysis, void content evaluation, and microstructural examination to assess the effects of filler concentration. The specimen with 12.5% PBF exhibited the highest void content (7.75%), while the neat epoxy sample showed the lowest (3.24%). An increasing trend in tensile strength was observed with higher PBF content, peaking at 24.172 MPa for the 12.5% PBF composite. Fatigue resistance improved with filler content; notably, the composite with 10% PBF endured over 10 ^6 fatigue cycles. Microstructural analysis revealed noticeable agglomeration of PBF particles in samples with filler content above 10%. The results suggest that incorporating powdered bamboo filler into epoxy composites can significantly enhance mechanical and fatigue properties, particularly up to a 10% filler concentration. However, excessive filler loading (beyond 10%) may lead to particle agglomeration and increased void content, which could negatively impact performance. These findings provide valuable insights for optimizing natural filler content in sustainable composite material design. The noted enhancements in tensile strength and fatigue life indicate that these composites may be appropriate for lightweight structural applications, especially in non-load-bearing scenarios.